The Synergistic Effect of Nitrogen Dopant and Calcination Temperature on the Visible-Light-Induced Photoactivity of N-Doped TiO2 - Yao-Tung Lin; Chih-Huang Weng; Hui-Jan Hsu; Yu-Hao Lin; Ching-Chang Shiesh (International Journal of Photoenergy)
The synergistic effect of nitrogen content and calcinations temperature on the N-doped TiO2 catalysts prepared by sol-gel method was investigated. The phase and structure, chemical state, optical properties, and surface area/pore distribution of N-doped TiO2 were characterized using X-ray diffraction spectrometer, high-resolution transmission electron microscope, X-ray photoelectron spectroscopy, UV-vis diffusion reflectance spectroscopy, and Brunauer-Emmett-Teller specific surface area. Finding showed that the photocatalytic activity of N-doped TiO2 was greatly enhanced compared to pure TiO2 under visible irradiation. N dopants could retard the transformation from anatase to rutile phase. Namely, N-doping effect is attributed to the anatase phase stabilization. The results showed nitrogen atoms were incorporated into the interstitial positions of the TiO2 lattice. Ethylene was used to evaluate the photocatalytic activity of samples under visible-light illumination. The results suggested good anatase crystallization, smaller particle size, and larger surface are beneficial for photocatalytic activity of N-doped TiO2. The N-doped TiO2 catalyst prepared with ammonia to titanium isopropoxide molar ratio of 2.0 and calcinated at 400°C showed the best photocatalytic ability.